Influence of contact parameters in fretting-fatigue contact 3D problems - Fella Hamadouche; Habib Benzaama; Mohamed Mokhtari; Miloud Abbes Tahar (Fracture and Structural Integrity)
A numerical study on the influence of contact parameters on fretting fatigue behavior is carried out by using a new method SFEM (Stretching Finite Element Method) is presented in this article. Several parameters are made to vary: geometric shapes of the mesh, materials and contact parameters. The three-dimensional parametric model is composed by specimen and a pad in full contact. A Fortran Code is used to generate the parametric mesh. The stress intensity factors are calculated by varying the above contact parameters and the stress intensity factor under modes I, II and III are computed..